Habitat for humanity and the mixed income housing market in Charlottesville - Mulloth, Bala (SAGE Knowledge. Cases., 2018)
This case addresses how the nonprofit, Habitat for Humanity, handled commercialization through mixed-revenue, mixed-income programming in Charlottesville, Virginia, USA. Four elements contributed to the successful adoption of mixed-revenue practices in the organization: the organization's prior business model; its relationship with the private sector; its programming; and its ethos.